Extra medullary multiple myeloma of knees: a case report - Bhalerao, Sagar; Adhav, Aditya; Nagarkar, Rajnish (International Journal of Research in Medical Sciences, 2019)
Multiple myeloma is defined as an incurable, complex, and rare malignant disease of the plasma cells. Multiple myeloma is characterized by uninhibited proliferation of clonal plasma cells. Extramedullary disease is characterized by the presence of clonal plasma cell infiltrate adjacent to soft tissues or distant from the bone marrow in patients with underlying MM. Survival of patients with MM is low. A 65-year-old female reports to the outpatient clinics with pain in the left lower limb for over 2 months. The patient had loss of range of motion. True-cut biopsy revealed multiple myeloma of synovial sarcoma. Extramedullary disease is considered as an uncommon manifestation of multiple myeloma. It is either a newly diagnosed disease or evolves with repeated relapses. There is no clear data on the incidence of extramedullary disease. Since there is a no standard treatment for extramedullary disease, its prognosis remains poor.